Job satisfaction and burnout of psychiatric nurses during the COVID-19 pandemic in China—the moderation of family support - Jin, Rui (Frontiers in Psychology, 2022)
Purpose: The study aimed at investigating the state of psychiatric nurses’ job satisfaction, job burnout, and the moderating effect of family support between them in China during the COVID-19 pandemic. Methods: Online self-report questionnaires were distributed and 212 psychiatric nurses participated in the research. Pearson correlation analysis, multiple stepwise regression analysis and simple slope test were used for data analysis. Results: The results showed that the status of their job satisfaction (53.67±10.72) and burnout (33.62±13.84) did not reach a satisfactory level and job satisfaction had a significant negative impact on job burnout. Meanwhile, family support played a negative moderating role between the two variables. Conclusions: Psychiatric nurses suffered from job burnout in China during the COVID-19. Family support could have a counterproductive effect when the nurses were experiencing decreasing job satisfaction. It gave suggestions to the medical institutions and the government to improve the psychological well-being of the psychiatric nurses and even of all the medical staff.